Efektivitas Program Mandiri Benih Padi di Kecamatan Ponrang Selatan - Hasri Hasri; Taruna S Arzam; Yumna Yumna (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This research was conducted in Ponrang Selatan District, Luwu Regency, South Sulawesi from March to September 2024. The population in this study were farmers who received benefits from the Mandiri Benih Activity. The sample in this study was 234 samples. The results of the study showed that the Mandiri Benih Padi program in Ponrang Selatan District began in 2022 and was expanded in 2023 by involving 42 farmer groups in various villages. Although this program has been running and received a positive response from farmers, there are still several aspects that are not optimal, especially in terms of certification of harvest results as seeds. The effectiveness value of 54.96 places the program in the